H. pylori Eradication Treatment Causes Alterations in the Gut Microbiota and Blood Lipid Levels - Martín-Núñez, Gracia M.; Cornejo-Pareja, Isabel; Roca-Rodríguez, M. del Mar; Clemente-Postigo, Mercedes; Cardona, Fernando; Fernández-García, José C.; Moreno-Indias, Isabel; Tinahones, Francisco J. (Frontiers in Medicine, 2020)
Background: The gut microbiome plays an important role in the development of diseases associated with altered lipid metabolis. Antibiotic treatment causes changes in the intestinal microbiota. Our aim was to evaluate the relationship between changes in the intestinal microbiota and the level of plasma HDL cholesterol and LDL cholesterol. Methods: Prospective case-control study with H. pylori-positive patients undergoing eradication therapy (omeprazole, clarithromycin, and amoxicillin). Stool and blood samples were obtained from 20 controls (H. pylori negative) and 40 patients before and two months after antibiotic treatment. Gut microbiota composition was analyzed through 16S rRNA amplicon sequencing (IlluminaMiSeq). Results: Eradication treatment for H. pylori increased the HDL- colesterol levels, and caused changes in gut microbiota profiles. An unfavorable lipid profiles (high LDL-cholesterol and low HDL-cholesterol level) was associated with a low microbial richness and an increased of the Bacteroidetes phylum. P. Copri, Lachonobacterium and Delsufovibrio were positively associated with HDL-c while Rikenellaceae was negatively associated with HDL-c after completing antibiotic treatment. Conclusions: Treatment to eradicate H. pylori could improve lipid metabolism in relation with an increase in the HDL-cholesterol. Changes in the abundance of specific bacteria, such as P. Copri, Lachonobacterium, Delsufovibrio and Rikenellaceae could be associated with change in the plasma HDL-cholesterol levels.